Comparative analysis of clinical efficacy of unilateral biportal endoscopic and open transforaminal lumbar interbody fusion in the treatment of lumbar degenerative - Ma, Tao; Tu, Xiaoshuang; Li, Junyang; Geng, Yongcun; Wu, Jingwei; Chen, Senlin; Yan, Dengming; Jiang, Ming; Gao, Gongming; Nong, Luming (Frontiers in Surgery, 2025)
ObjectiveTo study the clinical efficacy of unilateral biportal endoscopic lumbar interbody fusion (ULIF) and transforaminal lumbar interbody fusion (TLIF) in the treatment of lumbar degenerative diseases, and to compare perioperative indicators, radiological outcomes, and paraspinal muscle –atrophy resulting from these two different surgical methods.BackgroundTransforaminal lumbar interbody fusion (TLIF) is widely acknowledged as an efficacious surgical modality for alleviating low back pain. In recent years, unilateral biportal endoscopic lumbar interbody fusion (ULIF) has gained increasing application.MethodsWe recorded the basic information of patients who underwent single-segment ULIF or TLIF for the first time in our hospital from May 2021 to November 2022, including age, gender, BMI, diagnosis, and surgical segment. Perioperative indicators such as estimated blood loss, operation time, postoperative hospital stay, and complications were observed in both groups. Clinical efficacy was assessed preoperatively and at 1 month, 3 months, and 12 months postoperatively using the Visual Analogue Scale (VAS) and the Oswestry Disability Index (ODI). Patient satisfaction was evaluated using the modified Macnab criteria. The displacement of the fusion device was also assessed. x-rays were taken preoperatively, at 3 months postoperatively, and at 12 months postoperatively to observe fusion device displacement and measure the intervertebral disc height of the upper and lower segments. The Cobb angle was used to measure lumbar lordosis and segmental lumbar lordosis. CT scans at 3 months postoperatively were used to observe intervertebral fusion, including bridging trabeculae, endplate cysts, and screw loosening. MRI at 1 year postoperatively was used to manually trace the cross-sectional area of the paraspinal muscles to compare muscle atrophy.ResultsA total of 150 patients were included in the study, with 71 patients in the ULIF group and 79 patients in the TLIF group. No statistically significant disparities were observed between the two groups with respect to age, gender, BMI, diagnosis, and surgical segment. The estimated blood loss in the ULIF group was 108.78 ± 58.3 ml, which was significantly less than that in the TLIF group at 199.44 ± 84.91 ml (p < 0.001). The postoperative hospital stay was shorter in the ULIF group (p = 0.020), although the operation time was longer for ULIF. There were no significant differences in complications between the two groups. Patients in the ULIF group experienced quicker relief from back pain postoperatively, but there were no significant differences between the ULIF and TLIF groups in the VAS, ODI, and satisfaction rates at the final follow-up. At 3 months postoperatively, the ULIF group demonstrated a higher incidence of bridging trabeculae, a lower incidence of endplate cysts, and less fusion device displacement. There were no significant differences between the two groups in the correction of segmental lumbar lordosis (SL) and overall lumbar lordosis (LL). Additionally, the ULIF group showed less muscle damage.ConclusionULIF has the advantages of reducing pain in the short term, less blood loss, and shorter hospital stays. Its more precise handling of the intervertebral space reduces the occurrence of endplate cysts and fusion device displacement, which has certain significance in preventing delayed fusion and nonunion. However, ULIF requires a longer operation time, which increases potential risks for elderly patients or those with poor nutritional status. Although ULIF causes less damage to the bony structure, it has not shown a significant advantage in improving adjacent segment degeneration.